Transfer of fracture mechanical concepts to bulk solids attrition in pneumatic conveying - Peukert, Wolfgang; Frye, Lars (International Journal of Mineral Processing, 2004)
In the present project, attrition in pneumatic conveying—as in fracture mechanics and comminution—is regarded as a result of a process function (stress conditions) and a material function (influence of material properties). The first part of the paper describes the results of the determination of the stress conditions, where special emphasis is put on the numerical simulation of dilute-phase conveying. In the second part, results of single-particle tests are discussed. They simulate the two basic stress modes: impact and friction. The results show that the attrition behavior of the polymers tested changes between both stress modes. It is currently evaluated which material properties are suitable to describe this experimentally observed behavio
Keywords: Fracture mechanics: Computational fluid dynamics; Solid degradation; Pneumatic transport